Employment protection, labor market turnover, and the effects of globalization - Philip Schuster (Institute for Advanced Studies (IHS), 2012)
A parsimonious search and matching model of the labor market with endogenous separation is embedded in a North-North intermediate goods trade framework. International product market integration leads to redistribution of market shares from 'weak' to 'strong' firms within an industry, implying chances and threats for them, as firms are ex-ante unaware of their relative advantage over the competitor. Opening the economy will therefore increase the dispersion of potential revenues and consequently lead to higher labor market turnover, higher welfare and increased wage inequality, while the effect on employment is ambiguous. Ceteris paribus, the effects are qualitatively similar to decreasing employment protection in form of costly firing restrictions which prevent the economy from reaching a first best allocation. The positive welfare effects of opening to trade are decreasing in the level of firing costs. This can therefore lead to a substantial failure in reaping the benefits from economic integration.
Keywords: F15; F16; J63; J65; 330; employment protection; firing margin; trade in intermediate goods; labor market turnover; revenue risk